Reflections, or, Sentences and moral maxims - La Rochefoucauld, François, duc de, 1613-1680 (Open Road Integrated Media, Inc., 2017)
We all have strength enough to endure the misfortunes of others. This famed work by a noted French author of the Renaissance era, seventeenth-century nobleman Francois de La Rochefoucauld, offers hundreds of brief, brutally honest observations of humankind and its self-serving nature. The perfect read for any realist-or anyone with the desire to evaluate their moral standing-this edition includes three supplements with additional maxims and essays. This ebook has been professionally proofread to ensure accuracy and readability on all devices.